Education and training towards achieving Vision 2020 / Fong Chan Onn - Fong, Chan Onn (1992)
Vision 2020 is a goal which the country has set for itself - to join the ranks of industrialised countries by the year 2020. The Vision incorporates 9 challenges that the country must face in our quest to attain that status. Time would not permit me to discuss all the 9 challenges. This paper will therefore discuss the basic issues of economy and the role of education. Vision 2020, amongst other things, is about industrialisation to put the Malaysian economy on a firm footing so that it is capable of competing with the best in the world and is dynamic and resilient enough to stand up to the test of time and situation. Education and manpower training will have to play a pivotal role in this ambition. Aside from the materialistic sense so to speak, Vision 2020 takes a step further. The Vision lays out the country's aim to create a balanced development ie. the materialistic versus the social, ethical and moral development. We do not want to be respected only for our economic prowess, but also for our high moral and ethical standards. Education, undoubtedly plays an integral part in the pursuit of these objectives.